The Consumption of Lifetime and consumption habits in the face of pandemic - Staniszewska , Joanna (Research Papers in Economics and Finance, 2023)
The aim of this article is to present the concept of Consumption of Lifetime developed by the author and to show the impact of the phenomenon of digitalisation of society on decisions related to this concept. The author conducts an analysis in the context of consumption of lifetime to show the phenomenon of digitalisation and society’s consumption decisions. The process of digitalisation was particularly visible during the pandemic and the restrictions related to it, when education, work and interpersonal contacts were made possible with the use of devices connected to the Internet. These devices were also often used to make remote purchases. The implementation of the article made it possible to formulate research questions and conclusions that confirm the importance of considering decisions related to the consumption of lifetime in the period of ongoing digitalisation of society. Another interesting issue is the post-pandemic period, in which it is possible to observe whether consumption returns to the pre-pandemic state and previous purchasing behaviour. Currently, there is a noticeable tendency to return to the permanent consumption habits observed prior to the pandemic.